2021
DOI: 10.3389/fncel.2020.598198
|View full text |Cite
|
Sign up to set email alerts
|

P2RX7 in Dopaminergic Neurons of Ventral Periaqueductal Gray Mediates HTWP Acupuncture-Induced Consciousness in Traumatic Brain Injury

Abstract: The induction of a coma by traumatic brain injury (TBI) is a crucial factor for poor clinical prognoses. We report that acupuncture at the hand 12 Jing-Well points (HTWP) improved consciousness and neurologic function in TBI rats. Gene chip analyses showed that HTWP acupuncture mostly activated genes modulating neuronal projections (P2rx7, P2rx3, Trpv1, Tacr1, and Cacna1d), protein secretion (Exoc1, Exoc3l1, Fgb, and Fgr), and dopamine (DA) receptor D3 (Drd3) in the ventral periaqueductal gray (vPAG), among wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It is easy to develop into the second stage if not provided prompt and effective treatment, which causes a poor prognosis and low quality of life (QoL), bringing a huge economic burden to family and society. 4 Many studies 5 , 6 , 7 have proved that acupuncture was beneficial to TBI in brain function restoration and QoL improvement.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to develop into the second stage if not provided prompt and effective treatment, which causes a poor prognosis and low quality of life (QoL), bringing a huge economic burden to family and society. 4 Many studies 5 , 6 , 7 have proved that acupuncture was beneficial to TBI in brain function restoration and QoL improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Najem's study ( 43 ) indicated that acupuncture could reduce the efficacy of secondary brain injuries by reducing systemic and local inflammation, oxidative stress, intracellular calcium overload, neuronal regeneration, and growth factor release. Tang's research also revealed that acupuncture could activate genes modulating neuronal projections (P2rx7, P2rx3, Trpv1, Tacr1, and Cacna1d), protein secretion (Exoc1, Exoc3l1, Fgb, and Fgr), and dopamine (DA) receptor D3 (Drd3) in the ventral periaqueductal gray (vPAG), as well as the expression and excitability of DA and P2RX7 neurons ( 44 ). These may be the potential mechanisms of acupuncture for consciousness improvement in patients following stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Exocyst complex component 3 like 1 (EXOC3L1), also known as EXOC3L, is localized on chromosome 16 (16q22.1). Up to the present day, limited studies have shown that EXOC3L1 were involved in the regulation of insulin secretion ( Saito et al, 2008 ), protein secretion after traumatic brain injury ( Tang et al, 2020 ), spontaneous induction of apoptosis ( Matsumoto et al, 2021 ), and high-density lipoprotein concentration ( Lanktree et al, 2015 ), but the exact function of EXOC3L1 remains unclear. There are no reports on the study of EXOC3L1 in tumors so far, and the roles of EXOC3L1 in pan-cancer are far from clear, making it necessary to explore the role of EXOC3L1 in pan-cancer.…”
Section: Introductionmentioning
confidence: 99%